P21‐activated kinase 1 regulates resistance to BRAF inhibition in human cancer cells. Issue 5 (23rd February 2017) - Babagana, Mahamat; Johnson, Sydney; Slabodkin, Hannah; Bshara, Wiam; Morrison, Carl; Kandel, Eugene S.
Abstract : BRAF is a commonly mutated oncogene in various human malignancies and a target of a new class of anti‐cancer agents, BRAF‐inhibitors (BRAFi). The initial enthusiasm for these agents, based on the early successes in the management of metastatic melanoma, is now challenged by the mounting evidence of intrinsic BRAFi‐insensitivity in many BRAF‐mutated tumors, by the scarcity of complete responses, and by the inevitable emergence of drug resistance in initially responsive cases. These setbacks put an emphasis on discovering the means to increase the efficacy of BRAFi and to prevent or overcome BRAFi‐resistance. We explored the role of p21‐activated kinases (PAKs), in particular PAK1, in BRAFi response. BRAFi lowered the levels of active PAK1 in treated cells. An activated form of PAK1 conferred BRAFi‐resistance on otherwise sensitive cells, while genetic or pharmacologic suppression of PAK1 had a sensitizing effect. While activation of AKT1 and RAC1 proto‐oncogenes increased BRAFi‐tolerance, the protective effect was negated in the presence of PAK inhibitors. Furthermore, combining otherwise ineffective doses of PAK‐ and BRAF‐inhibitors synergistically affected intrinsically BRAFi‐resistant cells. Considering the high incidence of PAK1 activation in cancers, our findings suggests PAK inhibition as a strategy to augment BRAFi therapy and overcome some of the well‐known resistance mechanisms.